Web-Based Cognitive Training: Patient Adherence and Intensity of Treatment in an Outpatient Memory Clinic - Tedim Cruz, Vítor; Pais, Joana; Alves, Ivânia; Ruano, Luís; Mateus, Cátia; Barreto, Rui; Bento, Virgílio; Colunas, Márcio; Rocha, Nelson; Coutinho, Paula (JMIR Publications, 2014)
BackgroundCognitive training has been playing an increasing role in the treatment of patients with cognitive deficits. This type of intervention, namely its intensity, can be optimized by incorporating information technology-based systems. ObjectiveThe intent of the study was to determine the treatment intensity and patient adherence to home-based cognitive training strategies (Web-based cognitive training). MethodsA cohort of 45 patients with neurologic and psychiatric diseases attending an outpatient memory clinic (average age 50.7 years, SD 17.0; average education 7.8 years, SD 4.9) was followed over 18 months. Participants were challenged to use a Web-based cognitive training system, "COGWEB", on a daily basis, and fulfilled at least four weeks of training supervised remotely. Additionally, 11 patients attended face-to-face sessions. ResultsThe average duration of continuous cognitive training was 18.8 weeks (SD 18.9). Each patient performed on average 363.5 minutes/week (SD 136.6). At 6-month follow-up, 82.8% complied with their treatment plan. The average proportion of complete weeks was 0.75 (SD 0.22). Patients with dementia trained more intensively (444.6 minutes/week), followed by patients with static brain lesion (414.5 minutes/week; P=.01). The group that held face-to-face sessions performed more training overall (481.4 vs 366.9 minutes/week), achieving a stronger expression and statistical significance in the last week of training (652.6 versus 354.9 minutes/week, P=.027). ConclusionsOverall, the weekly training intensity was high. Patients with dementia and static lesions performed more cognitive training. Face-to-face sessions were associated with higher intensities. The combination of classical methods with information technology systems seems to ensure greater training intensity.